MEDIASI LITERASI KEUANGAN PADA PENGARUH FINTECH DAN INKLUSI KEUANGAN TERHADAP KINERJA UMKM - Farhan Wira Kusuma; Linzzy Pratami Putri (Value : Jurnal Manajemen dan Akuntansi, 2023)
MSMEs have positive benefits for the Indonesian economy until 2019 it is estimated that the number of MSMEs will grow to more than 65,400,000 units, MSMEs need to improve their financial performance by increasing financial literacy and using fintech and understanding financial inclusion. The purpose of conducting this research is to find out the effect of financial technology and financial inclusion on the performance of MSMEs mediated by financial literacy in Bandar Setia Village. This research uses a type of quantitative descriptive research and the nature of this research is explanatory research. This study has a population of 50 SMEs, where all populations are sampled in this study using a total sampling technique. The data analysis used is Partial Least Square analysis. The results of the study are: Financial Technology and Financial Inclusion have a positive and insignificant effect on the performance of MSMEs. Financial Technology and Financial Inclusion have a positive and significant effect on financial literacy on MSME performance. Financial literacy has a positive and insignificant effect on MSME performance. Financial Literacy does not mediate between Financial Technology and Financial Inclusion on MSME performance. Keywords: MSME performance, literacy, inclusion, fintech